2012
DOI: 10.1093/mollus/eys022
|View full text |Cite
|
Sign up to set email alerts
|

Two cryptic and sympatric species of Philinopsis (Cephalaspidea: Aglajidae) in the Bahamas distinguished using molecular and anatomical data

Abstract: Sequence data of nuclear and mitochondrial genes obtained from specimens of Philinopsis collected in the Bahamas revealed two genetically distinct groups. Further examination of the shell and male reproductive morphology revealed consistent anatomical differences between them, corroborating that they are distinct species. The two species also display consistent differences in external morphology and colour pattern that became evident only after the molecular information was analysed. A review of the literature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Taylor & Hellberg (2003, 2005 as a result of studies on reef fish provided the first molecular based support for this biogeographical break. Recent molecular systematics research on heterobranch sea slugs conducted by Ornelas-Gatdula et al (2011), Ornelas-Gatdula & Valdés (2012 and Carmona (2013) confirmed the presence of new cryptic species in the Bahamas not known elsewhere in the Caribbean province.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…Taylor & Hellberg (2003, 2005 as a result of studies on reef fish provided the first molecular based support for this biogeographical break. Recent molecular systematics research on heterobranch sea slugs conducted by Ornelas-Gatdula et al (2011), Ornelas-Gatdula & Valdés (2012 and Carmona (2013) confirmed the presence of new cryptic species in the Bahamas not known elsewhere in the Caribbean province.…”
Section: Introductionmentioning
confidence: 91%
“…When it comes to heterobranch sea slugs (the traditional opisthobranchs sensu Burn & Thompson, 1998), Valdés et al (2006) reported the occurrence of 308 species in the region and since then several others have been cited (e.g. Pola et al, 2008;Caballer & Ortea, 2011;Ornelas-Gatdula et al, 2011;Ornelas-Gatdula & Valdés, 2012;Ortigosa & Valdés, 2012). Likely the most comprehensive treatises about the Bahamian molluscs with focus on the northern island of Abaco are those of Redfern (2001Redfern ( , 2013 where 188 species of heterobranch sea slugs are cited (sensu traditional opisthobranchs; Redfern, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several recent works using molecular phylogenetics have showed that species of sea slugs regarded as highly variable in colour were in fact complexes of several species (e.g. Ornelas-Gatdula and Valdés 2012 [Philinopsis]; Carmona et al 2014b [Spurilla]), but there are also opposite examples; for instance, Malaquias et al (2016) have confirmed that distinct colour morphs of Chelidonura fulvipunctata are conspecific.…”
Section: Genus Odontoglaja Rudman 1978mentioning
confidence: 99%
“…The micro-speciation phenomenon is particularly evident in groups with non-planktotrophic development (Ornelas-Gatdula et al 2011;OrnelasGatdula and Valdés 2012), especially when studied as a whole in the area . The high rate of endemism observed may be the result of the isolation, caused by extensive open areas of "sterile" sands, which act as ecological barriers (Petuch 2013), or it may be explained by post-recruitment ecological factors, or historic vicariance (Ornelas-Gatdula and Valdés 2012;Carmona et al 2014).…”
Section: Introductionmentioning
confidence: 99%